2021
DOI: 10.1128/aac.02513-20
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Resistance Mediated by tet (M) Has Variable Integrative Conjugative Element Composition in Mycoplasma hominis Strains Isolated in the United Kingdom from 2005 to 2015

Abstract: A minimal genome and absent bacterial cell wall renders Mycoplasma hominis inherently resistant to most antimicrobials except lincosamides, tetracyclines and fluoroquinionlones. Often dismissed as a commensal (except where linked to preterm birth), it causes septic arthritis in immunodeficient patients and is increasingly associated with transplant failure (particularly lung) accompanying immunosuppression. We examined antimicrobial susceptibility (AST) on strains archived between 2005-2015 submitted to the Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…All characterized M. hominis and Ureaplasma spp. (predominantly from previously published investigations) 16,17,19 carrying the tet(M) resistance genes were identified correctly, in addition to four clinical M. hominis samples (19% WT prevalence of tetracycline resistance) with endogenous tet(M) and tetracycline resistance. Out of the 108 clinical samples with endogenous Ureaplasma spp., only 1 isolate was found to carry the tet(M) gene (MIC = 16 mg/L), as well as a second isolate with MIC = 2 mg/L (just at the threshold) that did not carry tet(M) resistance (2% WT prevalence of tetracycline resistance).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…All characterized M. hominis and Ureaplasma spp. (predominantly from previously published investigations) 16,17,19 carrying the tet(M) resistance genes were identified correctly, in addition to four clinical M. hominis samples (19% WT prevalence of tetracycline resistance) with endogenous tet(M) and tetracycline resistance. Out of the 108 clinical samples with endogenous Ureaplasma spp., only 1 isolate was found to carry the tet(M) gene (MIC = 16 mg/L), as well as a second isolate with MIC = 2 mg/L (just at the threshold) that did not carry tet(M) resistance (2% WT prevalence of tetracycline resistance).…”
Section: Discussionmentioning
confidence: 68%
“…moxifloxacin/levofloxacin resistance-mediating mutations in both the gyrA and parC genes. 19 Evaluating fluoroquinolone resistance in Ureaplasma spp. was more complicated, but not due to the MYCOPLASMA IST3 assay.…”
Section: Discussionmentioning
confidence: 99%
“…All M. hominis strains were inherently resistant to erythromycin and azithromycin (data not shown), mediated by the previously published inherent conserved polymorphism G2057A transition in their 23S rRNA sequences [ 20 ]. This cohort also included multi-drug resistant strains (Urogen006 and MH15-3) that are additionally resistant to all fluoroquinolones (mediated by S83L gyrA and S81I parC mutations) and tetracyclines (mediated by tet M) [ 21 ]. Susceptibility testing against lefamulin found no isolate to have an MIC >0.25 mg/L after 48 h incubation (range of 0.03–0.25 mg/L; MIC 50 of 0.06 and MIC 90 of 0.12 mg/L) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A panel of 90 isolated strains (25 Ureaplasma parvum , 25 Ureaplasma urealyticum , and 40 M. hominis ), characterised from previously published clinical cohorts [ 21 , 22 , 23 , 24 ] as well as from the UROGEN study (IRAS 251053; Spiller O.B. and Jones L.C.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of Tn916 conjugation genes precludes mobility, but the larger mosaic element retains competency for excision and circularization. It was subsequently shown that, in several M. hominis strains, this tet(M)-harboring transposon of variable length comprises a 13 kb region homologous to Tn916 and is consistently integrated between the somatic rumA gene and an hypothetical protein [83,84]. The tet(M) carrying Tn916 transposon is a notable exception, as there have been a limited number of mobile genetic elements in mycoplasmas described so far.…”
Section: Acquisition Of Mobile Genetic Elementsmentioning
confidence: 99%